High-resolution myelin water imaging in post-mortem multiple sclerosis spinal cord: A case report. (October 2016) - Laule, Cornelia; Yung, Andrew; Pavolva, Vlady; Bohnet, Barry; Kozlowski, Piotr; Hashimoto, Stanley A; Yip, Stephen; Li, David KB; Moore, GR Wayne
Background: Loss of myelin in the spinal cord in multiple sclerosis (MS) is likely an important, and early, contributor to atrophy and associated disability. In vivo measurement of myelin is possible using myelin water fraction (MWF) imaging, but MWF has never been assessed in MS along the entire length of the spinal cord in vivo or in post-mortem tissue. Objective: To assess the feasibility of measuring the distribution of MWF along the entire length of the spinal cord in post-mortem MS tissue using high-field MRI. Methods: One formalin-fixed spinal cord from a female with secondary progressive MS (age: 78 years, disease duration: 25 years) was cut into 104 5-mm-thick cross sections along the entire length of the spinal cord from the cervico-medullary junction to the conus medullaris and imaged using a 64 echo T2 relaxation experiment at 7T. Results: Myelin water maps showed cord anatomy in superb detail, white matter demonstrating a higher MWF than the grey matter. Anatomical variation in myelin distribution along cervical, thoracic and lumbar regions was observed. Lesions demonstrated myelin loss. Conclusion: Post-mortem myelin water imaging of formalin-fixed MS spinal cord is feasible.